2016
DOI: 10.1186/s12864-016-2670-x
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing-based detection of germline L1-mediated transductions

Abstract: BackgroundWhile active LINE-1 (L1) elements possess the ability to mobilize flanking sequences to different genomic loci through a process termed transduction influencing genomic content and structure, an approach for detecting polymorphic germline non-reference transductions in massively-parallel sequencing data has been lacking.ResultsHere we present the computational approach TIGER (Transduction Inference in GERmline genomes), enabling the discovery of non-reference L1-mediated transductions by combining L1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…None of these studies have yet shown clear evidence for de novo insertions, or “hopping,” of the retrotransposons in decedent patient tissues or laboratory models, though it is possible that improved methods for identifying somatic de novo insertions may shed more light on this possibility. As sequencing technologies improve with longer reads [142147], better protocols for transposon insertion profiling [146151], and better computational tools to handle repetitive genomic regions [148152], it may be easier to detect retrotransposon products ranging from specific loci generating elevated retrotransposon transcripts to polymorphic and de novo genome insertions.…”
Section: Discussionmentioning
confidence: 99%
“…None of these studies have yet shown clear evidence for de novo insertions, or “hopping,” of the retrotransposons in decedent patient tissues or laboratory models, though it is possible that improved methods for identifying somatic de novo insertions may shed more light on this possibility. As sequencing technologies improve with longer reads [142147], better protocols for transposon insertion profiling [146151], and better computational tools to handle repetitive genomic regions [148152], it may be easier to detect retrotransposon products ranging from specific loci generating elevated retrotransposon transcripts to polymorphic and de novo genome insertions.…”
Section: Discussionmentioning
confidence: 99%
“…The rarity of LINE-1-mediated pathogenic insertions described in the literature and in variant databases is attributable mostly to their low activity throughout the genome and to the technical difficulties in their detection (especially the full-length insertions). With massive parallel sequencing technology, there are also considerable limitations, particularly through short reads sequencing, and here, tailored bioinformatics analysis tools and strategies are required [ 22 ]. In the case of intronic LINE-1 insertions, detection may be hampered by the intron’s length and the fact that it mainly affects transcriptional events (e.g., intronic retentions or exonization events).…”
Section: Discussionmentioning
confidence: 99%